2013
DOI: 10.2166/washdev.2013.114
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of access to sanitation amongst low-income working women in Bangalore, India

Abstract: In India, access to sanitation amongst the urban poor remains low, and women are worse affected than men. Little is known about barriers to sanitation at the workplace, a location where working adults spend close to half of their waking hours. To explore access to sanitation facilities at the workplace amongst poor urban women, semi-structured interviews were conducted with 48 women working in low-income jobs in Bangalore. Access to sanitation varied by occupation group, with construction workers and domestic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Our participants alluded to upstream determinants of latrine ownership in several ways. They argued that non-adoption of latrines was not due to preferences but competing financial demands [14,15]; gender inequities that prioritized the wishes of the male head of household [55][56][57]; and the uncertainty of a post-construction reimbursement. Our work does not contradict other research that has found a preference for OD in rural India [16,18,26].…”
Section: Discussionmentioning
confidence: 99%
“…Our participants alluded to upstream determinants of latrine ownership in several ways. They argued that non-adoption of latrines was not due to preferences but competing financial demands [14,15]; gender inequities that prioritized the wishes of the male head of household [55][56][57]; and the uncertainty of a post-construction reimbursement. Our work does not contradict other research that has found a preference for OD in rural India [16,18,26].…”
Section: Discussionmentioning
confidence: 99%
“…(n = 38) Aguilar 2005; 49 Aihara 2016; 178 Andajani-Sutahjo 2015; 179 Arku 2010b; 180 Assaad 1994; 64 Baker 2017; 181 Bisung 2018; 182 Chew 2019; 183 Chipeta 2009; 72 Collins 2018; 184 (n = 34) Abu 2019; 62 Bisung 2016; 156 Boosey 2014; 197 Bora 2016; 198 Caruso 2017b; 170 Connolly 2013*; 199 Datta 2020; 200 Hall 2018; 201 Hirve 2015; 158 Jewitt 2014; 202 Joshi (n = 42) Abrahams 2006; 219 Alam 2017*; 220 Anyarayor 2019; 221 Bapat 2003; 154 Belur 2017*; 157 Bhatt 2019; 116 Camenga 2019; 222 Carolini 2012; 223 Caruso O'Reilly 2010; 48 Pardeshi 2009; 125 Rajaraman 2013; 236 Reddy 2019; 213 Rheinländer 2018*; 174 Routray 2015*; 168 Routray 2017a; 126 Sahoo 2015; 175 Schmitt 2017*; 214 Scorgie 2015*; 237 Senior 2014; 238 Shiras 2018; 161 Silva 2020; 215 Sommer 2015a; 239 Tegegne 2014*; 277 Thompson 2017; 217 Thuita 2017;…”
Section: A Bodily Integrity (N = 114)mentioning
confidence: 99%
“…(n = 34) Adrianessens 2019; 249 Azeez 2019; 114 Caruso 2017a; 224 Corburn 2015; 225 Corburn 2016; 226 ; Czerniewska 2019; 117 Hirai 2016; 120 Joshi 2018; 159 Khanna 2016; 121 Kulkarni 2017; 160 Kwiringira 2014; 172 Lee 2017; 122 Mohankumar 2017; 124 Oluyemo 2012; 56 O'Reilly 2010; 48 O'Reilly 2014; 140 Pardeshi 2009; 125 Prasad 2015; 282 Prasad 2018; 283 Rajaraman 2013*; 236 Reddy 2011; 212 Reddy 2019; 213 Routray 2017b; 110 Halvorson 2004; 104 Harris 2017; 82 Ilahi 2000; 281 Irianti 2019; 288 James 2002; 53 Joshi 2012; 203 Karim 2012; 246 Kher 2015; 230 Krumdieck 2016; 188 Lebel 2015; 83 Leder 2017; 45 MacRae 2019*; 164 Makoni 2004; 106 Mandara 2013; 84 Mason 2012; 86 Mbatha 2011; 206 McMahon 2011*; 207 Mehretu 1992; 263 Mehta 2015; 87 Mushavi 2020; 151 Narain 2014; 265 Nerkar 2013; 152 Oluyemo 2012; 56 Padmaja 2020; 89 Pommells 2018;…”
Section: CI Financial and Productive Assets (N = 118)mentioning
confidence: 99%
See 2 more Smart Citations